Submicron antibacterial material, preparation method of medical material doped with submicron antibacterial material and antibacterial catheter
By corroding carbon fiber into submicron structures and modifying flavonoid molecules, doped submicron antibacterial materials for the preparation of antibacterial catheters are prepared, which solves the short-term antibacterial properties of existing antibacterial catheters and may change urine fluid dynamics. The problem of this problem has achieved a long-term, stable and biosafe antibacterial effect.
Patent Information
- Application Number
- CN202411594550.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-09
- Publication Date
- 2025-02-18
AI Technical Summary
The antibacterial properties of existing antibacterial catheters are short-lived and unstable, and may change the urinary fluid dynamics. At the same time, the use of chemical antibacterial coatings has problems with allergic reactions and drug resistance.
Carbon fibers are used to form carbon powder with submicron structures through chemical corrosion, and flavonoid molecules are modified on its surface. Combined with the physical antibacterial properties of submicron structures and the chemical antibacterial mechanism of flavonoid molecules, we can prepare doped submicron antibacterial materials for In preparation of antibacterial catheters.
The long-term and stable antibacterial properties of antibacterial catheters are achieved, the use of chemical antibacterial agents is avoided, and the urinary fluid dynamics characteristics is not changed, ensuring the biosafety and controllable cost of the material.
Smart Images

Figure CN119453207A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical materials, and in particular relates to a submicron antibacterial material, a preparation method of a medical material doped with the submicron antibacterial material, and an antibacterial urinary catheter. Background Art
[0002] The incidence of catheter-associated urinary tract infection (CAUTI) has remained high for many years, and there is no effective countermeasure. It is a pain point that plagues the global medical and health industry. In my country, the incidence of urinary tract infection accounts for about 40% of hospital infections, and the proportion of hospital infections is high all year round, of which CAUTI accounts for 70-80% of urinary tract infections. The main reason for catheter-associated urinary tract infection is that the catheter is in an environment that is easily contaminated by bacteria during use. After the catheter is indwelling, its outer end is exposed to air and urine for a long time. Bacteria can retrograde along the urine into the part of the catheter located in the urethra, and bacteria can also invade between the outer surface of the catheter and the inner surface of the urethra. Bacteria easily and irreversibly attach to the inner and outer surfaces of the catheter, and secrete extracellular matrix to wrap the live bacteria, forming a highly structured membrane complex, namely a biofilm. The biofilm has poor permeability to antimicrobial drugs, which enhances the ability of bacteria to resist drugs and increases the risk of urinary tract infection. In recent years, with the emergence of new antibacterial materials, antibacterial catheters are expected to become one of the most effective strategies for preventing and treating catheter-related urinary tract infections. Therefore, it is of practical significance to develop a catheter with strong antibacterial properties, safety, stability and good biocompatibility.
[0003] Currently available antibacterial catheters are mainly divided into the following categories: ① Antibacterial layer applied on the surface, in which the antibacterial agents used are mainly quaternary ammonium salts, metal nanomaterials, antibiotics or antibacterial organic compounds; ② Silicone rubber grafted with antibacterial small molecules to prepare antibacterial catheters; ③ Inorganic antibacterial agents are added to the catheter material, that is, the antibacterial agent is added to silicone rubber to make antibacterial silicone rubber, and then the silicone rubber is molded into an antibacterial catheter; ④ Super-slip catheter: a hydrophobic molecular layer is applied on the surface of the catheter and lubricating oil is applied on the surface to inhibit or delay the formation of biofilm to reduce the risk of urinary tract infection; ⑤ A filter screen is installed near the bladder of the catheter to filter bacteria outside the catheter to prevent bacteria from entering the bladder and then entering the human body; ⑥ Physical methods are used to inhibit or delay the formation of biofilm on the inner surface of the catheter, that is, the structure of the catheter is redesigned and modified, and the flow rate of urine discharged into the catheter is controlled to delay the formation of biofilm on the inner surface of the catheter, thereby reducing the risk of urinary tract infection. However, some patients may have allergic reactions to antibiotics or heavy metal ions, and long-term use of antibiotic-coated catheters may cause bacteria to develop drug resistance and produce more serious infections. In addition, silver ion-coated antibacterial catheters are potentially toxic to the human body and cannot be metabolized due to the heavy metal properties of silver ions. Long-term accumulation is very harmful to the human body and is currently refused for use by many hospitals. In addition, although methods such as super-slip catheters and physical filtration have certain effects, the antibacterial and antibacterial functions of a single method are limited and cannot meet clinical needs. Finally, and more importantly, the antibacterial properties of the antibacterial catheters currently available on the market are short-lived and unstable, and may change the urine flow dynamics, causing more serious harm to the human body.
[0004] Therefore, there is an urgent need for an antibacterial catheter that has long-lasting and stable antibacterial properties, does not introduce chemical antibacterial agents, and does not change the urine flow dynamics characteristics. Summary of the invention
[0005] In view of the deficiencies in the above-mentioned prior art, the present invention provides a submicron antibacterial material, a method for preparing a medical material doped with a submicron antibacterial material, and an antibacterial catheter, so as to overcome the defects of the existing antibacterial catheters, namely, the antibacterial performance is short-lived, unstable, and may change the urine flow dynamics characteristics, while avoiding the problems caused by the use of chemical antibacterial agent coated catheters.
[0006] The present invention is based on the high strength, wear resistance, high temperature resistance and good biological safety of carbon fiber, and adopts a chemical method to corrode the carbon fiber into carbon powder with a submicron structure of different sizes and unevenness, and utilizes the special physical and mechanical effects of the submicron structure to destroy the bacterial structure, and the high strength and wear resistance of the carbon fiber to maintain the long-term effective antibacterial performance of the material; at the same time, it also utilizes the inhibitory effect of flavonoid molecules on a variety of bacteria, fungi and viruses, and modifies a small amount of flavonoid molecules on the surface of the submicron carbon powder. Through the physical antibacterial property of the submicron structure and the chemical antibacterial mechanism of the flavonoid molecules, a strong antibacterial performance is achieved, and the antibacterial performance is long-lasting and reliable.
[0007] The present invention provides a submicron antibacterial material, comprising: 4g-7g of submicron carbon powder, 0.5g-5.5g of polyethylene glycol, 0.1g-2.5g of flavonoid molecules, and 0.5g-2.4g of concentrated sulfuric acid with a mass fraction of 98%;
[0008] The submicron-sized carbon powder is formed by etching carbon fiber with a chemical etching agent, wherein the carbon fiber weighs 4g to 7g and the chemical etching agent weighs 200g to 700g.
[0009] The present invention provides a method for preparing a medical material doped with a submicron antibacterial material, the specific steps of which are:
[0010] S1, chemically corroding the carbon fiber to obtain submicron-sized carbon powder with a three-dimensional structure;
[0011] S2, modifying a small amount of flavonoid molecules on the surface of the submicron carbon powder prepared in step S1 to prepare submicron antibacterial carbon powder;
[0012] S3, adding submicron antibacterial carbon powder to the uncured medical rubber prepolymer, performing modified vulcanization treatment, and obtaining a medical material doped with submicron antibacterial material.
[0013] Preferably, the step S1 specifically comprises:
[0014] S11, immersing the carbon fiber in the prepared chemical corrosive agent, ultrasonically corroding in a water bath at 70-85°C for a period of time, and then cleaning the surface of the carbon fiber with deionized water to remove the residual corrosive solution;
[0015] S12, drying the cleaned carbon fiber to obtain submicron-sized carbon powder with a three-dimensional structure.
[0016] Preferably, the chemical corrosive agent in step S1 is one or more of concentrated hydrochloric acid, concentrated sulfuric acid, and concentrated nitric acid, the added mass ratio of carbon fiber to chemical corrosive agent is 1:(50-100), the corrosion time is 3-24h, and the size of submicron carbon powder is 100-1000nm.
[0017] Preferably, step S2 is specifically as follows: taking submicron carbon powder, adding deionized water, stirring thoroughly and then adding polyethylene glycol (molecular weight 20000), stirring thoroughly for a second time and heating in a water bath, then adding a small amount of flavonoid molecules to the solution, stirring and adding concentrated sulfuric acid with a mass fraction of 98%, adjusting the pH of the solution to between 7-7.5 after the reaction, and then placing the solution in a vacuum drying oven to dry, to obtain submicron antibacterial carbon powder.
[0018] Preferably, step S3 specifically comprises: adding submicron antibacterial carbon powder to uncured medical rubber prepolymer, blending through an internal mixer, and then adding a vulcanizing agent for vulcanization to obtain a medical material doped with submicron antibacterial material, wherein the added mass ratio of medical rubber: submicron antibacterial carbon powder: vulcanizing agent is 100:(0.1-1):(1-5).
[0019] Preferably, in step S2, the submicron carbon powder is 4g-7g, the deionized water is 50mL-150mL, the polyethylene glycol is 0.5g-5.5g, the water bath is heated at 80°C-100°C, the water bath is heated for 20min-60min, the flavonoid molecules are added in an amount of 0.1g-2.5g, stirred for 10min-30min, the amount of 98% concentrated sulfuric acid added is 0.5g-2.4g, the concentrated sulfuric acid with a mass fraction of 98% is added, reacted for 10min-60min, and dried in a vacuum drying oven for 6h-8h, the temperature of the vacuum drying oven is 80°C, and the negative pressure is 76cm Hg;
[0020] In step S3, the temperature of the internal mixer for blending is 20-80° C., the roller speed ratio is 1:(1-9), the blending time is 2-10 hours, the vulcanization temperature is 100-250° C., and the vulcanization time is 20-80 minutes.
[0021] Preferably, the carbon fiber in step S1 is polypropylene-based carbon fiber, modified polyvinyl chloride carbon fiber, fine-chain polyphenyl carbon fiber, vapor-phase synthesized carbon fiber or high-strength carbon fiber;
[0022] In step S2, the flavonoid molecule is 5-hydroxy-3',4',6,7-tetramethoxyflavone or 3',4',5,7-tetrahydroxyflavone;
[0023] In step S3, the medical rubber is medical silicone rubber, specifically one or more of dimethyl silicone rubber, methyl vinyl silicone rubber, methyl phenyl vinyl silicone rubber, and nitrile silicone rubber; the vulcanizing agent is one or more of diisopropylbenzene peroxide, 2,4-dichlorobenzoyl peroxide, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.
[0024] Preferably, the chemical corrosive agent is concentrated hydrochloric acid, and the added amount is 300g-400g.
[0025] The present invention also provides an antibacterial urinary catheter, the material of the urinary catheter is a medical material doped with submicron antibacterial material prepared by the preparation method described in the above technical solution.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. Based on the high strength, wear resistance, high temperature resistance and good biological safety of carbon fiber, the present invention adopts a chemical method to corrode the carbon fiber into carbon powder with a submicron structure of varying sizes and unevenness, and utilizes the special physical and mechanical effects of the submicron structure to destroy the bacterial structure. The high strength and wear resistance of carbon fiber maintain the long-term effective antibacterial properties of the material.
[0028] 2. The present invention utilizes the inhibitory effect of flavonoid molecules on a variety of bacteria, fungi and viruses, and modifies a small amount of flavonoid molecules on the surface of submicron-structured carbon powder. The physical antibacterial property of the submicron structure and the chemical antibacterial mechanism of the flavonoid molecules are combined to achieve a strong antibacterial performance, and the antibacterial performance is long-lasting and reliable. In addition, before modifying the flavonoid molecules, the present invention further disperses and dissolves the submicron-structured carbon powder in advance, so that the flavonoid molecules can be fully and evenly modified on the surface of the submicron-structured carbon powder, thereby further enhancing the antibacterial performance of the submicron-structured carbon powder.
[0029] 3. The raw materials used in the present invention, namely carbon materials and flavonoids, are green, environmentally friendly, widely available and inexpensive. At the same time, the production process does not involve any toxic reagents and has good biosafety.
[0030] 4. The antibacterial urinary catheter prepared by the present invention has the characteristics of good biosafety, stable and lasting antibacterial performance, controllable cost, simple manufacturing process, and mass production, and can be widely used in clinical practice as a medical device. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a flow chart of a method for preparing a medical material doped with a submicron antibacterial material in an embodiment of the present invention;
[0033] Figure 2 is an electron microscope image of the carbon fiber that has not been subjected to corrosion treatment in an embodiment of the present invention;
[0034] Figure 3 This is a magnified electron microscope image of submicron carbon powder after chemical etching in an embodiment of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific position, be constructed and operated in a specific position, and therefore cannot be understood as limiting the present invention; the terms "first", "second", and "third" are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance. In addition, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0037] The present invention provides a submicron antibacterial material, comprising: 4g-7g of submicron carbon powder, 0.5g-5.5g of polyethylene glycol, 0.1g-2.5g of flavonoid molecules, and 0.5g-2.4g of concentrated sulfuric acid with a mass fraction of 98%;
[0038] The submicron-sized carbon powder is formed by etching carbon fiber with a chemical etching agent, wherein the carbon fiber weighs 4g to 7g and the chemical etching agent weighs 200g to 700g.
[0039] like Figure 1 As shown, the present invention provides a method for preparing a medical material doped with a submicron antibacterial material, the specific steps of which are:
[0040] S1. Chemically corrode the carbon fiber to obtain submicron-sized carbon powder with a three-dimensional structure.
[0041] In this application, the step S1 is specifically:
[0042] S11. Immerse the carbon fiber in the prepared chemical corrosive agent, perform ultrasonic etching in a 70-85°C water bath for a period of time, and then use deionized water to clean the surface of the carbon fiber to remove the residual corrosive solution.
[0043] Since carbon fiber itself has high strength, wear resistance and high temperature resistance, it can withstand greater forces and friction, and can maintain antibacterial properties in high temperature environments, and is suitable for certain process requirements that need to be prepared in high temperature environments; at the same time, carbon fiber materials are relatively inert in terms of elemental properties, and are also one of the basic components of human tissues, with high safety, and are suitable for the preparation of biomaterials. Therefore, this application incorporates carbon fiber materials into the production of urinary catheters. In addition, considering the special physical and mechanical properties of submicron structures, this application prepares carbon fiber materials into submicron structural forms, using the special physical and mechanical effects of submicron structures to destroy bacterial structures, and the high strength and wear resistance of carbon fiber to maintain the long-term effective antibacterial properties of the material.
[0044] It should be noted that the special physical and mechanical properties of submicron structures are as follows: (1) They have a large specific surface area, which is beneficial to increase the surface area in contact with bacteria and enhance the antibacterial effect; (2) They can form tiny pores or protrusions to hinder the adhesion and growth of bacteria and act as a physical barrier; (3) The nanoscale or microscale concave-convex structure on the surface of the submicron structure can enhance the hydrophilicity of the material, making it difficult for bacteria to attach and grow on the surface; (4) They can be used as drug carriers to increase the drug loading and release efficiency and achieve better antibacterial effects.
[0045] In the present application, the carbon fiber is polypropylene-based carbon fiber, modified polyvinyl chloride carbon fiber, fine-chain polyphenyl carbon fiber, gas-phase synthesized carbon fiber or high-strength carbon fiber.
[0046] It should be noted that since the corrosion resistance, stability, biocompatibility, surface activity, controllability and physical antibacterial mechanism of modified polyvinyl ketone carbon fiber are better than other types of carbon fiber, the carbon fiber in the embodiment of the present application is preferably modified polyvinyl ketone carbon fiber.
[0047] The physical antibacterial mechanism performance of modified polyvinylpyrrolidone carbon fiber is specifically as follows: 1) Physical damage: Its surface characteristics may cause physical damage to the bacterial cell membrane, such as piercing or tearing the bacterial cell membrane, resulting in leakage of cell contents and cell death; 2) Electrochemical action: Its conductivity causes it to produce electrochemical action on the surface of the bacterial cell membrane, leading to potential imbalance of the cell membrane and destruction of ion channels, thereby destroying the integrity of the cell membrane; 3) Oxidation: Its surface is oxidizing and can undergo oxidation reactions with lipid molecules in the bacterial cell membrane, destroying the cell membrane structure; 4) Hydrophobic action: The hydrophobic nature of its surface causes it to interact with the lipid bilayer in the bacterial cell membrane, destroying the structure and function of the cell membrane.
[0048] In the present application, the chemical corrosive agent is one or more of concentrated hydrochloric acid, concentrated sulfuric acid, and concentrated nitric acid, the added mass ratio of carbon fiber to chemical corrosive agent is 1: (50-100), and the corrosion time is 3-24h.
[0049] Preferably, the chemical corrosive agent is concentrated hydrochloric acid, and the added amount is 300g-400g.
[0050] In the embodiment of the present application, in step S11, the carbon fiber is immersed in concentrated hydrochloric acid, ultrasonically corroded in a water bath at 80° C. for 20 hours, and then the surface of the carbon fiber is repeatedly cleaned three times with deionized water to remove residual corrosive liquid.
[0051] S12, drying the cleaned carbon fiber to obtain submicron-sized carbon powder with a three-dimensional structure.
[0052] like Figure 2-3 As shown, Figure 2 This is an electron microscope image of carbon fiber that has not been corroded. Figure 2 It can be seen that the untreated carbon fibers are basically cylindrical long fibers, with a fiber length of 20-200 microns and a fiber cross-section size of 5-11 microns; Figure 3 This is a magnified electron microscope image of submicron carbon powder after chemical etching. Figure 3 It can be clearly seen that there are many micro-nano sized protrusions on the surface of submicron carbon powder, with relatively sharp tops, which can cause mechanical damage to bacteria.
[0053] In the present application, the submicron carbon powder has a size of 100-1000 nm.
[0054] It should be noted that the size of submicron carbon powder is Figure 3 The dimensions of the fiber cross section.
[0055] S2. Modifying the surface of the submicron carbon powder obtained in step S1 with a small amount of flavonoid molecules to obtain submicron antibacterial carbon powder.
[0056] In the present application, the step S2 is specifically as follows: take submicron carbon powder and add deionized water, stir thoroughly and then add polyethylene glycol (molecular weight 20000), stir thoroughly for a second time and heat in a water bath, then add a small amount of flavonoid molecules to the solution, stir and add 98% concentrated sulfuric acid by mass, adjust the pH of the solution to between 7-7.5 after the reaction, and then place the solution in a vacuum drying oven to dry, to obtain submicron antibacterial carbon powder.
[0057] In this application, a chemical corrosion method is used to treat carbon fiber, so that the prepared carbon fiber has a special physical submicron structure, that is, the surface is corroded by chemical reagents to present an uneven shape, and there are many raised small thorns on the surface. When bacteria touch the submicron structure of carbon fiber, the bacterial membrane is punctured and the bacteria die. However, the antibacterial performance presented by this single antibacterial mechanism is weak, and specific molecules need to be modified on the surface to enhance the antibacterial performance of this submicron structure of carbon fiber.
[0058] In addition, the chemical method used to etch the carbon material in this application not only obtains submicron-sized carbon powder with a three-dimensional structure, but also obtains some carboxyl groups during the acidification process of the carbon fiber surface. The carboxyl groups have good activity and are conducive to enhancing subsequent surface modification or functionalization reactions.
[0059] Flavonoid molecules have inhibitory effects on a variety of bacteria, fungi and viruses. The main mechanism is to interfere with the bacterial cell membrane structure, block bacterial DNA synthesis, inhibit bacterial enzyme activity and regulate the intracellular environment of bacteria. Therefore, in this application, flavonoid molecules are added to enhance the antibacterial properties of submicron structured carbon fibers.
[0060] In addition, the submicrostructured carbon fiber with carboxyl groups undergoes an esterification reaction with the hydroxyl groups on the surface of the flavonoid molecules under the action of a catalyst, thereby covalently bonding the flavonoid molecules to the surface of the carbon fiber. Experimental studies have found that the flavonoid molecules chemically bonded to the surface of the carbon fiber are more active than the chemical reaction performance of the flavonoid molecules alone, and have stronger antibacterial properties than the flavonoid molecules alone. Therefore, in this application, by modifying the submicrostructured carbon fiber with carboxyl groups with flavonoid molecules, it is more conducive to obtaining a submicrostructured carbon fiber with strong antibacterial properties.
[0061] It should be emphasized that the antibacterial properties of flavonoid molecules themselves are not very strong, but in this application, a small amount of flavonoid molecules are modified on the surface of submicron-sized carbon powder, that is, carbon powder with specific structure and particle size is combined with flavonoid molecules to prepare carbon powder with strong antibacterial properties.
[0062] It should be noted that before modifying the flavonoid molecules on the surface of submicron carbon powder, the submicron carbon powder needs to be evenly dispersed in the solution in advance. Otherwise, the submicron carbon powder will precipitate in the solution, which will result in the flavonoid molecules being unable to be fully and evenly modified on the carbon fiber surface, thereby failing to prepare carbon fiber with strong antibacterial properties. Therefore, in this application, before adding the flavonoid molecules, the submicron carbon powder was dispersed and dissolved in advance using deionized water and polyethylene glycol.
[0063] In this application, the step S2
[0064] The submicron size carbon powder is 4g-7g, the deionized water is 50mL-150mL, the polyethylene glycol is 0.5g-5.5g, the water bath heating temperature is 80℃-100℃, the water bath is heated for 20min-60min, the flavonoid molecule is added in an amount of 0.1g-2.5g, stirred for 10min-30min, the mass fraction of 98% concentrated sulfuric acid is added in an amount of 0.5g-2.4g, the mass fraction of 98% concentrated sulfuric acid is added and reacted for 10min-60min, and dried in a vacuum drying oven for 6h-8h, the vacuum drying oven temperature is 80℃, and the negative pressure is 76cm Hg.
[0065] Preferably, in step S2, the submicron-sized carbon powder is preferably 4g-6g, the polyethylene glycol is preferably 0.8g-3g, the water bath heating temperature is preferably 90°C-100°C, the amount of flavonoid molecules added is preferably 0.5g-1.5g, the amount of 98% concentrated sulfuric acid added is preferably 0.7g-2g, the reaction time after adding 98% concentrated sulfuric acid is preferably 30min-60min, and the drying in the vacuum drying oven is preferably 7h-8h.
[0066] In the present application, the flavonoid molecule is 5-hydroxy-3',4',6,7-tetramethoxyflavone, or 3',4',5,7-tetrahydroxyflavone.
[0067] In the embodiments of the present application, the flavonoid molecule is preferably 5-hydroxy-3',4',6,7-tetramethoxyflavone.
[0068] S3, adding submicron antibacterial carbon powder to the uncured medical rubber prepolymer, performing modified vulcanization treatment, and obtaining a medical material doped with submicron antibacterial material.
[0069] In an embodiment of the present application, step S3 is specifically as follows: submicron antibacterial carbon powder is added to the uncured medical rubber prepolymer, blended by an internal mixer, and then a vulcanizing agent is added for vulcanization treatment to obtain a medical material doped with submicron antibacterial material, wherein the mixing temperature of the internal mixer is 20-80°C, the roller speed ratio is 1:(1-9), the mixing time is 2-10h, the vulcanization temperature is 100-250°C, and the vulcanization time is 20-80min.
[0070] In the embodiments of the present application, the temperature of the internal mixer is preferably 50-55°C, the roller speed ratio is preferably 1:(1-6.5), the blending time is preferably 2h-6h, the vulcanization temperature is preferably 120-200°C, and the vulcanization time is preferably 30-70min.
[0071] In the present application, the medical rubber is medical silicone rubber, specifically one or more of dimethyl silicone rubber, methyl vinyl silicone rubber, methyl phenyl vinyl silicone rubber, and nitrile silicone rubber.
[0072] In the present application, the vulcanizing agent is one or more of dicumyl peroxide, 2,4-dichlorobenzoyl peroxide, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.
[0073] In the present application, the addition ratio of medical rubber: submicron antibacterial carbon powder: vulcanizing agent is 100: (0.1-1): (1-5), preferably 100: (0.1-0.7): (1-4).
[0074] The present invention also provides an antibacterial urinary catheter, the material of the urinary catheter is a medical material doped with submicron antibacterial material prepared by the preparation method described in the above technical solution.
[0075] The present invention does not particularly limit the specific structure and size of the antibacterial urinary catheter provided, and those skilled in the art can design the structure of the urinary catheter and select the size of the urinary catheter according to actual needs. In addition, the urinary catheter provided by the present invention is hot-pressed in a mold.
[0076] For greater clarity, the present invention is described in detail by the following examples.
[0077] Example 1
[0078] 11) 4 g of carbon fiber is immersed in 400 g of chemical corrosive agent, and ultrasonically corroded in a 70° C. water bath for 24 hours, and then the surface of the carbon fiber is repeatedly cleaned three times with deionized water to remove residual corrosive solution, and the cleaned carbon fiber is dried to obtain a submicron-sized carbon powder with a three-dimensional structure, wherein the chemical corrosive agent is concentrated nitric acid; in addition, step 11) is repeated multiple times to collect the dry submicron-sized carbon powder for later use.
[0079] 12) Take 4 g of submicron carbon powder and add it to 50 mL of deionized water. After stirring thoroughly, add 1 g of polyethylene glycol (molecular weight 20,000). After stirring twice, heat it in a water bath at 80°C for 60 min. Then add 0.5 g of 3',4',5,7-tetrahydroxyflavone to the solution. After stirring for 10 min, add 2.4 g of 98% concentrated sulfuric acid. After reacting for 10 min, adjust the pH of the solution to 7. Then, place the solution in a vacuum drying oven and dry it for 6 h to obtain submicron antibacterial carbon powder. The vacuum drying oven temperature is 80°C and the negative pressure is 76 cmHg.
[0080] 13) Methyl vinyl silicone rubber and submicron antibacterial carbon powder are mixed in an internal mixer, and a vulcanizing agent diisopropylbenzene peroxide is added for vulcanization treatment to obtain a medical material doped with submicron antibacterial material, wherein the addition ratio of methyl vinyl silicone rubber: submicron antibacterial carbon powder: vulcanizing agent is 100:0.1:5, the mixing temperature of the internal mixer is 80°C, the roller speed ratio is 1:9, the mixing time is 2h, the vulcanization temperature is 250°C, and the vulcanization time is 20min.
[0081] Example 2
[0082] Different from Example 1, the amount of carbon fiber added is 7g, the amount of chemical corrosive added is 700g, the amount of submicron size carbon powder added is 7g, deionized water is 150mL, the amount of polyethylene glycol (molecular weight is 20000) added is 5.5g, 100℃ water bath heating for 20min, stirring for 30min, the amount of 98% concentrated sulfuric acid added is 0.5g, the reaction time of 98% concentrated sulfuric acid by mass fraction is 60min, the pH of the solution is adjusted to 7.5, dried in a vacuum drying oven for 8h, the mixing temperature of the internal mixer is 20℃, the roller speed ratio is 1:1, the mixing time is 10h, the vulcanization temperature is 100℃, and the vulcanization time is 80min.
[0083] Example 3
[0084] The difference from Example 1 is that the amount of chemical corrosive agent added is 200 g, ultrasonic etching is carried out in a water bath at 85° C. for 18 h, the amount of polyethylene glycol (molecular weight 20,000) added is 3 g, heating is carried out in a water bath at 90° C. for 40 min, 5-hydroxy-3',4',6,7-tetramethoxyflavone is selected as the flavonoid molecule and the amount added is 1.5 g, the amount of 98% concentrated sulfuric acid added is 1.5 g, the reaction time of 98% concentrated sulfuric acid is 35 min, the pH of the solution is adjusted to 7.3, and the solution is dried in a vacuum drying oven for 7 h.
[0085] Example 4
[0086] The difference from Example 1 is that ultrasonic etching is performed in a 75°C water bath for 22 hours, the amount of submicron-sized carbon powder added is 5.5 g, deionized water is 100 mL, the amount of polyethylene glycol (molecular weight is 20,000) added is 4 g, and the mixture is heated in a 90°C water bath for 40 minutes. The flavonoid molecule is 5-hydroxy-3',4',6,7-tetramethoxyflavone and the amount added is 2.5 g. The mixture is stirred for 15 minutes. The vulcanizing agent is 2,4-dichlorobenzoyl peroxide, and the addition ratio of methyl vinyl silicone rubber: submicron antibacterial carbon powder: vulcanizing agent is 100:1:3.
[0087] Example 5
[0088] Different from Example 1, the chemical corrosive agent is concentrated sulfuric acid, the medical rubber is dimethyl silicone rubber, and the addition ratio of dimethyl silicone rubber: submicron antibacterial carbon powder: vulcanizing agent is 100:0.5:1.
[0089] Example 6
[0090] Different from Example 2, the chemical corrosive agent is concentrated sulfuric acid, ultrasonic etching is performed in a water bath at 85° C. for 3 h, the medical rubber is nitrile silicone rubber, and the addition ratio of nitrile silicone rubber: submicron antibacterial carbon powder: vulcanizing agent is 100:0.5:3.
[0091] Example 7
[0092] The difference from Example 1 is that the chemical corrosive agent is concentrated hydrochloric acid, ultrasonic etching is performed in a water bath at 80°C for 20 hours, the amount of 3',4',5,7-tetrahydroxyflavone added is 1 g, the mixing temperature of the internal mixer is 50°C, the roller speed ratio is 1:5, the mixing time is 6 hours, the vulcanization temperature is 180°C, and the vulcanization time is 60 minutes.
[0093] Example 8
[0094] The difference from Example 1 is that the amount of carbon fiber added is 5 g, the chemical corrosive agent is concentrated hydrochloric acid and the amount added is 300 g, and the ultrasonic etching is carried out in a water bath at 80°C for 20 h; the amount of submicron carbon powder added is 5 g, deionized water is 100 mL, the amount of polyethylene glycol (molecular weight is 20000) added is 1.5 g, and the water bath is heated at 90°C for 30 min, the amount of 3',4',5,7-tetrahydroxyflavone added is 0.8 g, and it is stirred for 20 min. The mass fraction of concentrated sulfuric acid is 1.3 g, and the mass fraction of 9 is 98%. The reaction time of 8% concentrated sulfuric acid is 50 minutes, the pH value of the solution is adjusted to 7.35, and it is dried in a vacuum drying oven for 8 hours; the medical rubber is methylphenyl vinyl silicone rubber, the vulcanizing agent is 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, the addition ratio of methylphenyl vinyl silicone rubber: submicron antibacterial carbon powder: vulcanizing agent is 100:0.1:4, the mixing temperature of the internal mixer is 50°C, the roller speed ratio is 1:5, the mixing time is 6 hours, the vulcanization temperature is 180°C, and the vulcanization time is 60 minutes.
[0095] Example 9
[0096] Different from Example 8, the addition ratio of methylphenyl vinyl silicone rubber: submicron antibacterial carbon powder: vulcanizing agent is 100:0.2:4.
[0097] Example 10
[0098] Different from Example 8, the addition ratio of methylphenyl vinyl silicone rubber: submicron antibacterial carbon powder: vulcanizing agent is 100:0.3:4.
[0099] Embodiment 11
[0100] Different from Example 8, the addition ratio of methylphenyl vinyl silicone rubber: submicron antibacterial carbon powder: vulcanizing agent is 100:0.4:4.
[0101] Comparison Example
[0102] The methylphenyl vinyl silicone rubber and the vulcanizing agent 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane were blended in an internal mixer, wherein the addition ratio of the methylphenyl vinyl silicone rubber vulcanizing agent was 1:0.85, the blending temperature of the internal mixer was 50°C, the drum speed was 1:5, the blending time was 6h, the vulcanization temperature was 180°C, and the vulcanization time was 60min.
[0103] It should be noted that in order to detect the effect of the submicron antibacterial carbon content on the performance of the antibacterial catheter, the present application refers to the method specified in the national recommended standard GB / T 31402-2015 "Test Method for Antibacterial Performance of Plastic Surfaces", and uses Staphylococcus aureus ATCC6538 and Escherichia coli ATCC8739 as indicator bacteria to perform antibacterial testing on the antibacterial catheters prepared in Examples 8-11 and the control example. The testing steps are as follows:
[0104] (1) High-pressure steam sterilization: Examples 8-11 were used as sample groups, and the control example was used as a blank control group. Twelve 5 cm × 5 cm flat plates of antibacterial urinary catheters were prepared and placed in a high-pressure steam sterilizer and sterilized at (121 ± 2) °C for 15 min or more.
[0105] (2) Dilute the bacterial suspension with 1 / 500 NB to a bacterial concentration of 2.5×10 5 CFU / mL~10×10 5 CFU / mL, used as inoculum, and the bacterial count was determined by the counting plate method.
[0106] (3) Sample inoculation: Place a 5 cm × 5 cm plate in a sterile culture dish. Use a pipette to draw up 0.4 mL of inoculation solution and drop it onto the surface of each sample. Place a 4 cm × 4 cm film on the inoculated bacterial solution and gently press the film to allow the bacterial solution to spread around to ensure that the bacterial solution does not overflow from the edge of the film. Finally, cover the culture dish.
[0107] (4) Cultivation: Cultivate at (35±1)°C and relative humidity not less than 90% for (24±1) h.
[0108] (5) Place the test sample group and the blank control group in a 37°C incubator for 48 hours and observe the results.
[0109] (6) Recover the bacterial strains separately and calculate the recovery rate.
[0110] According to GB / T 31402-2015, if the antibacterial rate tested in a certain period of time is ≥90%, it can be judged that the plastic product has a continuous antibacterial effect during this period of time. In this application, the antibacterial rate test results of Examples 8-11 and the control example are shown in Table 1.
[0111] Table 1. Antibacterial rate test table of Examples 8-11 and control examples
[0112]
[0113] As can be seen from Table 1, in Examples 8-11, due to the addition of submicron antibacterial carbon powder, the produced catheters exhibited excellent antibacterial properties. Specifically, the antibacterial rates of these catheters against Escherichia coli and Staphylococcus aureus reached 90% or more, and the submicron antibacterial carbon powder began to show an excellent antibacterial rate of 99.99% when the addition ratio was 0.3. This result shows that the addition of submicron antibacterial carbon powder significantly enhanced the antibacterial ability of the catheter. In contrast, the catheter in the control example did not add submicron antibacterial carbon powder, but only used ordinary silicone rubber material. Therefore, its antibacterial rate failed to reach 90% or more, indicating that the catheter does not have effective antibacterial properties. Therefore, the submicron antibacterial carbon powder prepared in this application has good antibacterial properties in the production process of the catheter.
[0114] In the present application, reference is also made to GB / T528-1998 "Test of tensile strain energy of vulcanized rubber or thermoplastic rubber", GB / T529-1998 "Determination of tear strength of vulcanized rubber (right angle type)", and GB / T531-1998 "Test method for Shore A hardness of vulcanized rubber", and the physical and mechanical properties of Examples 8-11 and the control examples are tested. The test results are shown in Table 2.
[0115] Table 2. Physical and mechanical properties test table of Examples 8-11 and Control Examples
[0116]
[0117] As can be seen from Table 2, the physical and mechanical properties of the catheters produced in Examples 8-11 with the addition of submicron antibacterial carbon powder all meet the national standard requirements and have good physical and mechanical properties. Although it can be clearly seen from Table 2 that the physical and mechanical properties of the catheters produced in the control examples without submicron antibacterial carbon powder are slightly better than those in Examples 8-11, it can be seen from Table 1 that Examples 8-11 have slightly lower physical and mechanical properties while also meeting good antibacterial properties, while the control examples are only superior in physical and mechanical properties but do not have antibacterial properties. Therefore, the submicron antibacterial carbon powder prepared in this application is indispensable in the production process of catheters.
[0118] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A submicron antibacterial material, characterized in that: include: Submicron carbon powder 4g-7g, polyethylene glycol 0.5g-5.5g, flavonoid molecules 0.1g-2.5g, and concentrated sulfuric acid with a mass fraction of 98% 0.5g-2.4g; The submicron-sized carbon powder is formed by etching carbon fiber with a chemical etching agent, wherein the carbon fiber weighs 4g to 7g and the chemical etching agent weighs 200g to 700g.
2. A method for preparing a medical material doped with a submicron antibacterial material, characterized in that: The specific steps are: S1, chemically corroding the carbon fiber to obtain submicron-sized carbon powder with a three-dimensional structure; S2, modifying a small amount of flavonoid molecules on the surface of the submicron carbon powder prepared in step S1 to prepare submicron antibacterial carbon powder; S3, adding submicron antibacterial carbon powder to the uncured medical rubber prepolymer, performing modified vulcanization treatment, and obtaining a medical material doped with submicron antibacterial material.
3. The method for preparing a medical material doped with a submicron antibacterial material according to claim 2, characterized in that: The step S1 is specifically as follows: S11, immersing the carbon fiber in the prepared chemical corrosive agent, ultrasonically corroding in a water bath at 70-85°C for a period of time, and then cleaning the surface of the carbon fiber with deionized water to remove the residual corrosive solution; S12, drying the cleaned carbon fiber to obtain submicron-sized carbon powder with a three-dimensional structure.
4. The method for preparing a medical material doped with a submicron antibacterial material according to claim 3, characterized in that: In step S1, the chemical corrosive agent is one or more of concentrated hydrochloric acid, concentrated sulfuric acid, and concentrated nitric acid. The added mass ratio of carbon fiber to chemical corrosive agent is 1: (50-100), the corrosion time is 3-24h, and the size of submicron carbon powder is 100-1000nm.
5. The method for preparing a medical material doped with a submicron antibacterial material according to claim 4, characterized in that: The step S2 is specifically as follows: taking submicron carbon powder and adding it to deionized water, stirring it thoroughly and then adding polyethylene glycol (molecular weight of 20,000), stirring it twice and then heating it in a water bath, then adding a small amount of flavonoid molecules to the solution, stirring and then adding concentrated sulfuric acid with a mass fraction of 98%, adjusting the pH of the solution to between 7 and 7.5 after the reaction, and then placing the solution in a vacuum drying oven to dry, so as to obtain submicron antibacterial carbon powder.
6. The method for preparing a medical material doped with a submicron antibacterial material according to claim 5, characterized in that: The step S3 specifically comprises: adding submicron antibacterial carbon powder to uncured medical rubber prepolymer, blending through an internal mixer, and then adding a vulcanizing agent for vulcanization to obtain a medical material doped with submicron antibacterial material, wherein the added mass ratio of medical rubber: submicron antibacterial carbon powder: vulcanizing agent is 100:(0.1-1):(1-5).
7. The method for preparing a medical material doped with a submicron antibacterial material according to claim 6, characterized in that: In the step S2, the submicron carbon powder is 4g-7g, the deionized water is 50mL-150mL, the polyethylene glycol is 0.5g-5.5g, the water bath is heated at 80°C-100°C, the water bath is heated for 20min-60min, the flavonoid molecules are added in an amount of 0.1g-2.5g, stirred for 10min-30min, the amount of 98% concentrated sulfuric acid added is 0.5g-2.4g, the concentrated sulfuric acid with a mass fraction of 98% is added, reacted for 10min-60min, and dried in a vacuum drying oven for 6h-8h, the vacuum drying oven temperature is 80°C, and the negative pressure is 76cm Hg; In step S3, the temperature of the internal mixer for blending is 20-80° C., the roller speed ratio is 1:(1-9), the blending time is 2-10 hours, the vulcanization temperature is 100-250° C., and the vulcanization time is 20-80 minutes.
8. The method for preparing a medical material doped with a submicron antibacterial material according to claim 7, characterized in that: In step S1, the carbon fiber is polypropylene-based carbon fiber, modified polyvinyl chloride carbon fiber, fine-chain polyphenyl carbon fiber, vapor-phase synthesized carbon fiber or high-strength carbon fiber; In step S2, the flavonoid molecule is 5-hydroxy-3',4',6,7-tetramethoxyflavone or 3',4',5,7-tetrahydroxyflavone; In step S3, the medical rubber is medical silicone rubber, specifically one or more of dimethyl silicone rubber, methyl vinyl silicone rubber, methyl phenyl vinyl silicone rubber, and nitrile silicone rubber; the vulcanizing agent is one or more of diisopropylbenzene peroxide, 2,4-dichlorobenzoyl peroxide, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.
9. The method for preparing a medical material doped with a submicron antibacterial material according to claim 8, characterized in that: The chemical corrosive agent is concentrated hydrochloric acid, and the added amount is 300g-400g.
10. An antibacterial urinary catheter, wherein the material of the urinary catheter is a medical material doped with a submicron antibacterial material obtained by the preparation method according to any one of claims 2 to 9.